2008
DOI: 10.1080/09658210701864580
|View full text |Cite
|
Sign up to set email alerts
|

H.M.'s personal crossword puzzles: Understanding memory and language

Abstract: The amnesic patient H.M. has been solving crossword puzzles nearly all of his life. Here, we analyzed the linguistic content of 277 of H.M.'s crossword-puzzle solutions. H.M. did not have any unusual difficulties with the orthographic and grammatical components inherent to the puzzles. He exhibited few spelling errors, responded with appropriate parts of speech, and provided answers that were, at times, more convincing to observers than those supplied by the answer keys. These results suggest that H.M.'s lexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Relative sparing of skills such as ability to play music or games has been described even in patients with advanced AD (Cowles et al, 2003; Baird & Samson, 2009), which could result from enhanced cognitive reserve or sparing of brain areas serving these skills by disease pathology. Similarly, the medial temporal structures affected early in the course of AD do not appear to be critical in preserving ability to do crossword puzzles (Skotko, Rubin, & Tupler, 2008) and mental representations learned previously could help anchor new semantic knowledge (Skotko et al, 2004). We also note the case of the famous amnesiac patient, H.M., who lost his ability to remember new events and facts after bilateral medial temporal resection during epilepsy surgery; strikingly, his language ability and performance of standard motor tasks acquired before surgery remained intact (Corkin, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Relative sparing of skills such as ability to play music or games has been described even in patients with advanced AD (Cowles et al, 2003; Baird & Samson, 2009), which could result from enhanced cognitive reserve or sparing of brain areas serving these skills by disease pathology. Similarly, the medial temporal structures affected early in the course of AD do not appear to be critical in preserving ability to do crossword puzzles (Skotko, Rubin, & Tupler, 2008) and mental representations learned previously could help anchor new semantic knowledge (Skotko et al, 2004). We also note the case of the famous amnesiac patient, H.M., who lost his ability to remember new events and facts after bilateral medial temporal resection during epilepsy surgery; strikingly, his language ability and performance of standard motor tasks acquired before surgery remained intact (Corkin, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Third, because the field has recognized the theoretical significance of speech errors since Lashley [ 13 ], why did the many researchers interacting informally with H.M. since then overlook his aphasia-like errors and assume that his language skills were “normal” or even “erudite” (see [ 14 ])?…”
Section: Introductionmentioning
confidence: 99%
“…In literature, there is the report of a patient with amnesia who solved 277 crosswords; by analyzing such crosswords solved, the researchers found that patients had a greater number of errors (54%) to complete the crossword puzzle that had hints horizontally, compared with those displayed vertically (45%). However, researchers justify that difference may only be a matter of personal preference on how to solve the puzzle, since the patient studied solved the tips arranged in horizontal lines before the vertical lines (SKOTKO, RUBIN and TUPLER, 2008).…”
Section: Discussionmentioning
confidence: 99%